Analisis Perbandingan Nilai Proyek Dengan Standar Nasional Indonesia (SNI) dan Harga Satuan Pokok Kegiatan (HSPK) (Studi Kasus: SDN Kedung Cowek Baru) - Widodo, Sofian Agus; Yakin, Kusnul; Nugroho, Wisnu Abiarto (Universitas Dr. Soetomo, 2020)
The budget is an estimate of the costs to be incurred for a particular business project. Here it is discussed about the unit price of various kinds of work and materials that will be used in a construction. Because estimates are made prior to the start of construction, the costs obtained are estimated costs, not actual costs for a project later. The study was conducted on the project of SDN Kedung Cowek Baru in Surabaya there was a budget planning made by the contractor. The problem in this research is how the writer to get the value of the comparison and the difference in the budget. So this research focuses on the aim to produce a comparison of the value of the project with a planned budget using the analysis of SNI and HSPK in 2016. Data processing on the RAB calculation uses the SuperRAB software. After getting the results from the SuperRAB software, then comparing the value of the project budget between the contractor, SNI, and HSPK. Based on processing using HSPK 2016 analysis produces a value of Rp 1.788.763.474,49, an analysis of SNI 2016 produces a value of Rp.1.512.242.079,60, and a contractor analysis produces a value of Rp.764.935.498,42, If the three analysis results are compared, produces the percentage of HSPK 2016 43,99%, SNI 2016 18,82%, contractors 37,19%. The difference between the largest analysis of HSPK 2106 and the smallest analysis from the contractor is Rp. 1.023.827.976,07. The large difference in value is influenced by the unit price of materials and wages used.